Financing Renewable Energy in Namibia - A Fundamental Key Challenge to the Sustainable Development Goal 7: Ensuring Access to Affordable, Reliable, Sustainable and Modern Energy for All - Amesho, Kassian T.T.; Edoun, Emmanuel Innocents (International Journal of Energy Economics and Policy, 2019)
Renewable energy has been a "hot topic" subsequently the increased awareness and understanding of the severe and serious effects of climate change. Like many developing countries across the globe and Africa in particular, Namibia is prone to such climate changes and, thus, should be more familiarized with the impacts of fossil fuel generation on the environment. Successful significant financial and technological investments in renewable energy (RE) in Namibia needs a comprehensive understanding of the correlation among diverse categories of investors and their enthusiasm to finance renewable energy. Contrariwise, using the Sustainable Development Goal 7: Ensure Access to Affordable, Reliable, Sustainable and Modern Energy for All, as a measure for a wide-ranging and sustainable growth we recognize the interaction values that comes with renewable energy. We studied the asset portfolios of diverse renewable energy technologies supported or subsidized by various financial actors in Namibia. We also related the performance of public and private types of investments and then discrete further with various financial actors (e.g. public banks, private banks, international climate finance) and the categories of RE technologies that are financed in (e.g. different types of energy production from wind, biomass or solar radiation). We then use these preliminary results to draw conclusion and suggestions on how investment impact the directionality of novelty, and the impacts on RE policy in Namibia. This study establishes that notwithstanding the apparent regulatory and economic challenges, Namibia can incorporate and use a blend of (restructured) energy price security structures, cross subsidizations and environmental taxes in-order to encourage initiatives intended at supplementary the country's progress of renewable energy sources and hence ultimately support the UN Sustainable Energy for All Initiative. Keywords: renewable energy finance, financial actors, climate finance, energy access, renewable energy policy. JEL Classifications: Q2, Q54 DOI: https://doi.org/10.32479/ijeep.7704